Flower attractiveness and nectar accessibility for Delia radicum (Diptera:Anthomyiidae) with implications for the control by Trybliographa rapae (Hymenoptera:Figitidae) - Rännbäck, Linda-Marie (2008)
Conservation biological control aims at preserving populations of natural enemies in and around crop fields. Resources of floral nectar are important to natural enemies to increase the longevity, fecundity and motivation to seek host insects. Floral nectar for hymenopteran parasitoid wasps is investigated in a literature study, which suggests plant species to include in flower strips. However it is important to ensure that the plant species are selective towards natural enemies and not favor pest insects in addition. The aim of this Master thesis is to study the attraction to and nectar accessibility of dill, Anethum graveolens (Apiaceae); buchwheat, Fagopyrum esculentum (Polygonaceae) and alyssum, Lobularia maritima (Brassicaceae) for the severe crucivorous pest Delia radicum. The ambition is ultimately to find plants species selectively suitable as nectar sources for the parasitoid wasp Trybliographa rapae. The three plants species investigated were found to be both attractive and having accessible nectar to D. radicum. The flower attractiveness experiments revealed significant attraction, where the preference was L. maritima > A. graveolens > F. esculentum. When given a choice between L. maritima (food plant) and cauliflower (host plant), there was a tendency of preference for L. maritima. The plant species had accessible nectar and gave a weight increase after 1, 6 and 12 hrs. After 1 h, L. maritima and F. esculentum gave an equal increase, which was significantly higher than for A. graveolens. Volatile collections of the highly attractive L. maritima were made and revealed six common compounds; toluene; limonene; 2-ethylhexyl acetate; 2-ethyl-1-hexanol; benzaldehyde; and 2-hydroxy-benzaldehyde. These compounds could be observed in a ratio of 17:1:1:2:2:1.